Peanut Processing Characteristics and Quality Evaluation - Wang, Qiang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book systematically covers the sensory, physical, chemical nutrition, and processing characteristics of different peanut varieties, while also providing an in-depth review of research advances in peanut processing quality. The book goes on to examine the relationship between raw materials and the qualities of peanut protein, peanut oil and other main peanut processing products. As such, it provides a valuable reference guide for research into the raw materials, change mechanisms and control technologies used in peanut processing, laying the groundwork for the development of new disciplines in "grain and oil processing quality". It will be useful for graduate students, researchers, and management groups from multidisciplinary audiences, covering both food science & technology and public health.
Chapter 1 Overview of Peanut Processing Quality.- Chapter 2 Quality Characteristics and Determination Methods of Peanut Raw Materials.- Chapter 3 Quality Characteristics of Peanut Products.- Chapter 4 Relationship between Raw Material Quality and Product Quality of Peanut.- Chapter 5 Peanut Processing Suitability Evaluation Standards.- Chapter 6 Functional Improvement of Peanut Protein Concentrate -- Chapter 7 Improvement of Gelation of Peanut Protein Isolate -- Chapter 8 Gelation Improvement of Peanut Protein Component -- Chapter 9 Preparation of Functional Peanut Oligopeptide and its Biological Activity -- Chapter 10 Oxidation Stability Improvement of Peanut Oil.
Keywords: Food science; Food Science